Variasi gen Angiotensin converting enzyme (ACE) pada kinerja ledakan atlet bulu tangkis - Arimbi, Arimbi; Hasmyati, Hasmyati; Syahruddin, Syahruddin; Arfanda, Poppy Elisano; Wahid, Wahyana Mujari (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
The appropriate genetic potential of an athlete or prospective athlete determines the development of their future performance and achievement and reduces the risk of pathological conditions such as overtraining. This study aimed to determine the genotype variation thought to play a role in differences in exercise results and explosive power performance, namely the ACE gene. The research method used a cross-sectional design to describe the relationship between a factor and its effects on how genetic mutation variations play a role in an athlete's physical performance by involving 54 male and female badminton athletes with an average age of 18 years. The study was conducted by analysing the development of badminton skills with the same exercise routine, then being given an explosive power test in the form of a vertical jump through the Lewis nomogram assessment. The initial test was in the first month, and the second test was after six months. The results showed significant differences between the groups with variation II, ID and DD genotypes of the ACE gene. The DD genotype group showed better training adaptation in the explosive power test than genotype II and ID with a significant value (P<0.05). This study concludes that athletes with genotype DD variations adapt better to explosive power training than athletes with genotype II and ID. Athletes with genetic mutations II and ID in the ACE gene are more suitable for badminton sports requiring complex movement abilities and skills, which require good anaerobic and aerobic abilities.